Serial Kasus : Presentasi Klinis dan Tata Laksana Nodul Endometriosis Subkutan - Franciska, Shelly; Harzif, Achmad Kemal; Lethulur, Shindie Dona Kezia (Jurnal Kedokteran Meditek, 2025)
Introduction: Subcutaneous endometriosis is a rare condition with endometrial tissue localized outside the pelvis and often mimics general endometriosis. The novelty of this study is an in-depth understanding of the specific risk factors associated with subcutaneous endometriosis after cesarean section and how optimal therapeutic approaches can provide better outcomes in patients with a history of endometriosis. This study aims to explore the clinical presentation, outcomes, and managerial approaches to this condition, as well as provide evidencebased recommendations for its management. Case Illustration: This study involved seven patients at Cipto Mangunkusumo Hospital (January 2022–December 2024). Data collected included demographics, age, BMI, initial symptoms, time of symptom onset, history of cesarean section, history of endometriosis, complications, nodule size, therapeutic approaches, and clinical outcomes. Discussion: Of the seven patients, three underwent one cesarean section, two underwent two operations, and two underwent more than two cesarean sections. A history of diffuse adenomyosis was found in three patients. Subcutaneous nodules located mainly in the cesarean scar, had highly variable sizes and caused significant pain (VAS 5–6). Dienogest therapy was given to three patients and significantly reduced pain. Conclusion:Subcutaneous endometriosis is often associated with a history of abdominal surgery, especially cesarean section. Extrapelvic location can be mistaken for keloid or fibroma, which hinders timely diagnosis. The novelty of this study lies in emphasizing the importance of multidisciplinary collaboration in the management of subcutaneous endometriosis, especially involving plastic surgeons to improve aesthetic results and prevent recurrence. Treatment involving hormonal therapy or surgery, based on the size and location of the nodule, is essential for optimal results.